Changes in the Release of Endothelial Extracellular Vesicles CD144+, CCR6+, and CXCR3+ in Individuals with Acute Myocardial Infarction - Alexa Moreno; Pedro Alarcón-Zapata; Enrique Guzmán-Gútierrez; Claudia Radojkovic; Héctor Contreras; Estefanía Nova-Lampeti; Felipe A. Zúñiga; Llerenty Rodriguez-Alvárez; Carlos Escudero; Paola Lagos; Claudio Aguayo (Biomedicines)
Acute myocardial infarction (AMI) results from vulnerable plaque rupture, causing ischemic cardiomyocyte necrosis and intense inflammation. Paradoxically, this inflammation releases factors that aid heart repair. Recent findings suggest a role for extracellular vesicles (EVs) in intercellular communication during post-AMI cardiac repair. However, EVs’ tissue origin and chemokine profile in the blood of patients with AMI remains unclear. This study characterized the tissue origin and chemokine receptor profile of EVs in the coronary and peripheral blood of patients with AMI. The results reveal that vesicles isolated from coronary and peripheral blood plasma are enriched in tetraspanin (CD9) and express CD81+, CD90+, and CD144+. The vesicle size ranged between 145 and 162 nm, with the control group exhibiting smaller vesicles (D10) than the AMI group. Furthermore, all vesicles expressed CCR6 and CXCR3, whereas a small percentage expressed CCR4. In addition, a decrease in CXCR3 and CCR6 expression was observed in coronary and peripheral AMI blood vesicles compared with the control; however, no difference was found between AMI coronary and AMI peripheral blood vesicles. In conclusion, our study demonstrates, for the first time, changes in the number of extracellular vesicles expressing CD144+, CXCR3, and CCR6 in the peripheral circulation of patients with AMI. Extracellular vesicles present in the circulation of patients with AMI hold excellent promise as a potential diagnostic tool.